MONETARY INCOMES OF THE POPULATION IN RUSSIA AND NOVOSIBIRSK AREA - G.P. Litvintseva (Экономика региона, 2016)
This paper presents the results of research level of monetary incomes, an inequality and poverty of the population in the Russian Federation and Novosibirsk area taking into account purchasing capacity of ruble in region.